Selective gas-phase conversion of maleic anhydride to propionic acid on Pt-based catalysts - Regenhardt, Silvina Andrea (2013)
Pt-based catalysts, supported on Al2O3, SiO2 and SiO2-Al2O3, were prepared by incipient wetness impregnation and tested in the gas phase hydrogenation of maleic anhydride at atmospheric pressure and 240 °C. In these conditions, the hydrogenolytic activity pattern was: Pt/SiO2 > Pt/Al2O3 > Pt/SiO2-Al2O3, which is just the opposite of the support acidity trend. These metal Pt-based catalysts showed high selectivity to propionic acid, which was always higher than 80%. The selectivity pattern to this product was: Pt/Al2O3 > Pt/SiO2 > Pt/SiO2-Al2O3. Both activity and selectivity patterns may be explained on the basis of metal-support interaction and support acidity.